Penile fracture: A rare case of simultaneous rupture of the one corpus cavernosum and complete urethral rupture - Nale Đorđe; Bojanić Nebojša; Nikić Predrag (Vojnosanitetski Pregled)
Introduction. Penile fracture is a traumatic rupture of tunica albuginea and the tumescent corpora cavernosa due to the nonphysiological bending of the penile shaft, presenting with or without rupture of corpus spongiosum and urethra. The incidence of concomitant injury of the urethra is 0-38%. Complete urethral rupture is rare, but it is almost always associated with bilateral corporeal injury. Case report. We presented a patient with complete urethral rupture, and rupture of the right cavernous body. According to the available literature, this case is extremely rare. Conclusion. Fracture of the penis is relatively uncommon and is considered a urologic emergency. Prompt surgical exploration and repair can preserve erectile and voiding function.